Age-associated declining of the regeneration potential of skeletal stem/progenitor cells - Mancinelli, Luigi; Intini, Giuseppe (Frontiers in Physiology, 2023)
Bone fractures represent a significant health burden worldwide, mainly because of the rising number of elderly people. As people become older, the risk and the frequency of bone fractures increase drastically. Such increase arises from loss of skeletal integrity and is also associated to a reduction of the bone regeneration potential. Central to loss of skeletal integrity and reduction of regeneration potential are the skeletal stem/progenitor cells (SSPCs), as they are responsible for the growth, regeneration, and repair of the bone tissue. However, the exact identity of the SSPCs has not yet been determined. Consequently, their, functions, and especially dysfunctions, during aging have never been fully characterized. In this review, with the final goal of describing SSPCs dysfunctions associated to aging, we first discuss some of the most recent findings about their identification. Then, we focus on how SSPCs participate in the normal bone regeneration process and how aging can modify their regeneration potential, ultimately leading to age-associated bone fractures and lack of repair. Novel perspectives based on our experience are also provided.